Implementasi Metode Discovery Inquiry Dalam Meningkatkan Kemampuan Berpikir Siswa Pada Pembelajaran Pendidikan Agama Islam Bagi Siswa Smp Swasta Tunas Mandiri Tanjung Pura - Marhan Hasibuan; Ahmad Darlis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
Implementation of the Discovery Inquiry method in improving students' thinking skills in learning Islamic religious education for students of Tunas Mandiri Private Junior High School Tanjung Pura. This study uses quantitative research methods. The location of the research was carried out at the Tunas Mandiri Private Junior High School, Tanjung Pura District, Langkat Regency. The implementation of this research was carried out from April to June 2021. The purpose of this study was to determine the implementation of Discovery Inquiry in improving students' thinking skills in learning Islamic religious education for students of Tunas Mandiri Private Junior High School Tanjung Pura, Langkat Regency, whether there is a significant relationship significant. To prove this, the author conducted a study on the title. This research was conducted on 30 students of Tunas Mandiri Private Junior High School Tanjung Pura which were used as research samples. Data collection tools are library research, observation, questionnaires and interviews. The results of the questionnaire were processed by tabulating the data to determine the frequency. Based on the discussion of the research results in this thesis, it can be seen that the implementation of the Discovery Inquiry method for students of Tunas Mandiri Private Junior High School Tanjung Pura is very good (70%). Meanwhile, students' thinking ability in learning Islamic religious education for students of Tunas Mandiri Private Junior High School Tanjung Pura is good (73.3%). The results of the tabulation calculation between the implementation of the Discovery Inquiry method on students' thinking abilities in learning Islamic religious education for students of Tunas Mandiri Private Junior High School Tanjung Pura with a moderate or adequate level of significance.